Development of Community-based Early Warning System Against Debris Flow, Mt. Merapi - Legono, Djoko; Rahardjo, Adam Pamudji; Fathani, Teuku Faisal; Prabowo, Irawan Eko (2008)
Mt. Merapi, which is laid at Central Java Province and Yogyakarta Special Province, is one of some active volcanoes in the world, with the high population at its surrounding. In almost every eruption period, Mt. Merapi produces large number of sediment volume in which could move downstream in various ways or mechanisms, such as landslides and debris avalanche. Furthermore, such material migrates downstream through the steep slope torrential streams in what it is called debris flow. Such debris flow may contribute the destructive power then causing damage on the river banks, bridges, houses, etc. It was reported that the 2006 Mt. Merapi eruption (from April thru October 2006), has produced approximately 8.0 million m3 of sediment, potentially to move downstream towards the southern part of the mountain. A number of 600,000 m3 debris avalanche in the form of hot pyroclastic material flown down in June 14, 2006 in less than two hours, devastating tourist area and two casualties. There was no rainfall occurrence has been found to trig the phenomenon, it means the debris avalanche is purely caused by instability of the lava dome. In almost all cases of the occurrence of the debris avalanche, rainfall at certain intensity contributes significant influence on its phenomenon. Therefore, the prediction of the debris flow occurrence in the stream may be approximated through identifying the rainfall characteristics at the corresponding catchment area. This paper presents the result of the study on the correlation between the rainfall characteristics with the occurrence of the debris avalanche at Mt. Merapi area, Indonesia. The study covers the characteristic of Mt. Merapi sediment in various conditions such as its distribution, slope instability parameters, as well as property change due to its variation in time. The rainfall characteristics study is focused in the short duration intensity in several locations at Mt. Merapi area. The result is anticipated to contribute necessary information for the development of the community-based debris flow early warning system. Keywords: community-based, debris flow disaster, Early Warning System (EWS)